Framings of abortion in Pacific Island print media: qualitative analysis of articles, opinion pieces, and letters to the editor - Burry, Kate; Beek, Kristen; Worth, Heather; Vallely, Lisa; Haire, Bridget (Sexual and reproductive health matters, 2023)
Abortion is significantly restricted by law in most Pacific Island countries, and this has profound implications for the lives and health of women from this region. There are limited data on how abortion is framed in the Pacific Islands: that is, interpreted, discussed, and made meaningful as an issue in public forums. How abortion is framed can have implications for how it is treated in public and political debate and policy, abortion stigmatisation, and inform advocacy strategies. We undertook a thematic analysis of 246 articles, opinion pieces, and letters to the editor that covered the topic of abortion in mainstream print media. We found three dominant framings. Abortion was often positioned in opposition to gender ideology and national identity, with gender and national identity constructed by many commentators according to socially conservative, Christian doctrine. Abortion was also constructed as the killing of the "unborn," with the fetus positioned as the key social subject. Alternatively, abortion was framed as often unsafe and a response to teenage pregnancy, with various solutions suggested in this context. Few commentators constructed women who experienced unwanted pregnancies and abortions as making decisions about their pregnancies in response to complex gendered and socio-economic conditions. Dominant framings of abortion as opposed to gender ideals, nationalism, and the killing of the "unborn" complicate simplified appeals to "choice" in advocacy efforts. Focusing on health and broader injustice experienced by women offer alternative framings.